2013
DOI: 10.1590/s1806-66902013000100008
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da colheita mecanizada de feijão (Phaseolus vulgaris) em dois sistemas de preparo do solo

Abstract: Palavras-chave:Controle estatístico de processo (CEP). Desempenho operacional. Perdas na colheita. Recolhedoratrilhadora.ABSTRACT -Among the production stages of the bean plant, harvesting is one of the most important, because it can decisively affect both quality and production costs. Thus, the objective was to assess quality in the mechanized harvesting of beans (Phaseolus vulgaris), grown under conventional tillage and no-tillage systems. The variables analysed were: the noise level emitted, calculated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
26

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 13 publications
0
16
0
26
Order By: Relevance
“…Thus, in the treatments of combined operations and left side of the mechanized fertilization, the coefficients of asymmetry and kurtosis were close to 0, showing normal distribution, however with two operations and the right side of the fertilization operation showed higher values, rebounding with an asymmetric distribution, obtaining more dispersed values. Silva et al (2013), also found that some of the analyzed variables had normal distribution by the normality test, so the same showed in the descriptive analysis median values close to the average; the standard deviation with low value; the Cs had a positive asymmetric distribution (Cs>0) and small (|Cs|<0.15), the Ck showed leptokurtic distribution (Ck>0), that is, more concentrated and platykurtic data (Ck<0) with concentrated values. These authors also cited the variables with positive asymmetric distribution (Cs>0) and high (|Cs|>1), as a consequence, the average value was far from the median and the total amplitude with high variability.…”
Section: Descriptive Statistics Of Potassium Chloride Distributionmentioning
confidence: 52%
“…Thus, in the treatments of combined operations and left side of the mechanized fertilization, the coefficients of asymmetry and kurtosis were close to 0, showing normal distribution, however with two operations and the right side of the fertilization operation showed higher values, rebounding with an asymmetric distribution, obtaining more dispersed values. Silva et al (2013), also found that some of the analyzed variables had normal distribution by the normality test, so the same showed in the descriptive analysis median values close to the average; the standard deviation with low value; the Cs had a positive asymmetric distribution (Cs>0) and small (|Cs|<0.15), the Ck showed leptokurtic distribution (Ck>0), that is, more concentrated and platykurtic data (Ck<0) with concentrated values. These authors also cited the variables with positive asymmetric distribution (Cs>0) and high (|Cs|>1), as a consequence, the average value was far from the median and the total amplitude with high variability.…”
Section: Descriptive Statistics Of Potassium Chloride Distributionmentioning
confidence: 52%
“…However, most of these variables had 5 to 10% of their points outside the control limits, whereas the rotor speed (at 5 km h -1 ) and grain moisture content (at 7 km h -1 ) had 50% and 35% of their points outside the control limits, respectively. Considering the high variability usually observed for quality indicators in a harvesting process (Silva et al, 2013b), the quantity of points observed outside the control limits was low and therefore did not indicate real process instability.…”
Section: -Clustering; M -Mixture; T -Trend; O -Oscillation;mentioning
confidence: 95%
“…Most studies used control charts to identify the occurrence of special causes Silva et al, 2013b;Voltarelli et al, 2013Voltarelli et al, , 2014Voltarelli et al, , 2015Noronha et al, 2011;Custodio et al, 2012). Chioderoli et al (2012) reported that control charts can be used efficiently to evaluate the quality of Felipe B. F. de Lima, Michel A. F. da Silva, Rouverson P. da Silva, et al Eng.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, the tool typically used to identify non-random causes or special causes arising from instability of the process are the individual values of control charts (CHIODEROLI et al, 2012;COMPAGNON et al, 2012;CASSIA et al, 2013;SILVA et al, 2013;VOLTARELLI et al, 2013;ZERBATO et al, 2013;VOLTARELLI et al, 2014).…”
Section: Introductionmentioning
confidence: 99%